Molecular profiling and bioactive potential of an endophytic fungus Aspergillus sulphureus isolated from Sida acuta: a medicinal plant - M. Murali; C. Mahendra; P. Hema; N. Rajashekar; A. Nataraju; M. S. Sudarshana; K. N. Amruthesh (Taylor & Francis Group, 2017)
Context: Sida acuta Burm.f. (Malvaceae) extracts are reported to have applications against malaria, diuretic, antipyretic, nervous and urinary diseases. No fungal endophytes of S. acuta are reported. Objective: Isolation, identification and evaluation of antibacterial, antioxidant, anticancer and haemolytic potential of fungal endophytes from the ethnomedcinal plant S. acuta. Materials and methods: Sida acuta stem segments were placed on PDA medium to isolate endophytic fungi. The fungus was identified by genomic DNA analysis and phylogenetic tree was constructed using ITS sequences (GenBank) to confirm species. The antibacterial efficacy of Aspergillus sulphureus MME12 ethyl acetate extract was tested against Gram-positive and Gram-negative pathogenic bacteria. DPPH free radical scavenging activity, anticancer and DNA fragmentation against EAC cells, and direct haemolytic activity (100-500 μg/mL) using human erythrocytes were determined. Results and discussion: The ethyl acetate extract of A. sulphureus (Fresen.) Wehmer (Trichocomaceae) demonstrated significant antibacterial potential against Staphylococcus aureus, Bacillus subtilis, Escherichia coli and Salmonella typhi compared to streptomycin. MIC against test pathogens was in the range of 15.6-62.5 μg/mL. The antioxidant results revealed significant RSA from 12.43% to 62.02% (IC50 = 350.4 μg/mL, p ≤ 0.05). MME12 offered considerable inhibition of EAC proliferation (23% to 84%, IC50 = 216.7 μg/mL, p ≤ 0.05) supported by DNA fragmentation studies. The extract also offered insignificant haemolysis (5.6%) compared to Triton X-100. Conclusions: A single endophytic fungus, A. sulphureus MME12 was isolated and identified using molecular profiling. The above-mentioned findings support the pharmacological application of A. sulphureus MME12 extract and demand for purification of the active principle(s).